2020
DOI: 10.1002/uog.22070
|View full text |Cite
|
Sign up to set email alerts
|

Second‐ and third‐trimester serum levels of growth‐differentiation factor‐15 in prediction of pre‐eclampsia

Abstract: Objective Pre‐eclampsia (PE) is a significant contributor to adverse maternal and perinatal outcome; however, accurate prediction and early diagnosis of this condition remain a challenge. The aim of this study was to compare serum levels of growth‐differentiation factor‐15 (GDF‐15) at three different gestational ages between asymptomatic women who subsequently developed preterm or term PE and healthy controls. Methods This was a case–control study drawn from a prospective observational study on adverse pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
(56 reference statements)
1
17
0
Order By: Relevance
“…Pooled results with ten studies [24][25][26][27][28][29][30][31] showed that compared to controls of women with normal pregnancy at least matched for GA, women with preeclampsia had significantly higher circulating level of GDF-15 at the diagnosis of the disease (SMD: 0.66, 95 % CI: 0.16 to 1.17, p = 0.01, I 2 = 93 %; ▶Fig. 2a).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pooled results with ten studies [24][25][26][27][28][29][30][31] showed that compared to controls of women with normal pregnancy at least matched for GA, women with preeclampsia had significantly higher circulating level of GDF-15 at the diagnosis of the disease (SMD: 0.66, 95 % CI: 0.16 to 1.17, p = 0.01, I 2 = 93 %; ▶Fig. 2a).…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…3b, p for subgroup difference > 0.05). Moreover, meta-analysis with three studies [26,31,32] also showed a higher level of GDF-15 was before the diagnosis in women who subsequently developed preeclampsia than those who did not (SMD:…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GDF15, as a member of the transforming growth factor (TGF)-β superfamily (Mullican et al 2017), is expressed at the undetectable level under normal physiological in most somatic tissues of human, but, in some pathological conditions, such as inflammation and cancer, its expression level is highly increased, and especially, it is abundantly expressed by the syncytiotrophoblast (STB) in placenta (Wischhusen et al 2020). Although the association of circulating level of GDF15 in the second and third trimester with the PE (Wertaschnigg et al 2020) or pregnancy-associated vomiting (Petry et al 2018) has been evaluated, however, the association of its circulating level in the first trimester with RM has not yet been reported. ITIH3 belongs to the ITIH gene family, and ITIHs play important roles in inflammation and carcinogenesis in humans (Hamm et al 2008), as well as in the maintenance of the uterine surface glycocalyx during placenta development in pig (Geisert et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, other recent works found increased serum GDF15 at 30-34 weeks in those destined to develop early onset preeclampsia, but no significant change at 35-37 weeks prior to preeclampsia at term. 64 The most important difference between these studies was the use of plasma in one, and serum in the other. Caution must be exercised when using different sample types for comparison or validation of biomarkers.…”
Section: Placental Proteinsmentioning
confidence: 99%